Using 3D Animation and Virtual Reality in Educations - Mustafa, Bahaa (Technium Social Sciences Journal, 2022)
This paper will look at the use of innovative and advanced technology teaching methods to support the goal of learning enhancement by using established teaching concepts. The primary aim is to explore the potential for using leading-edge virtual reality technology to help students learn and understand various concepts. The utility of the technology was examined by studying the latest 3D programming tools. Additionally, there were several styles of animation used. The results showed that Virtual Reality technologies can play a role in education and learning when supported by established learning and teaching concepts.